145 TARGETING BCL-2 IN ACUTE MYELOID LEUKEMIA CELLS. (1st January 2006) - Simms-Waldrip, T.; Hernandez, J.; Shankar, D.; Moore, T. B.; Sakamoto, K. M.
Abstract : Purpose of Study: Proteins of the Bcl-2 family members are critical regulators of programmed cell death, and members that inhibit apoptosis, including Bcl-2 and Bcl-XL, are overexpressed in many cancers and contribute to tumor initiation, progression, and resistance to therapy. ABT-737 is a small molecule inhibitor of Bcl-2, Bcl-XL, and Bcl-w that was identified using nuclear magnetic resonance-based screen, parallel synthesis, and structure-based design. Previous studies revealed that this inhibitor does not initiate apoptosis but enhances the effects of death signals and acts synergistically with chemotherapy and radiation to induce cytotoxicity. ABT-737 as a single agent kills cells from lymphoma and small cell lung carcinoma lines in vitro and in vivo. In this study, we investigated the effects of ABT-737 on three different human acute myeloid leukemia (AML) cell lines. Methods: Two human AML cell lines, KG-1 and MV-411, were treated with varying concentrations of ABT-737 ranging from 1 pM to 10 μM in complete media containing 10% fetal calf serum (FCS). Another human AML cell line, Molm-13, was treated with ABT-737 at concentrations ranging from 1 nM to 10 μM in media containing either 10% FCS or 1% FCS. Percent viability was determined using trypan blue exclusion at 24, 48, 72 hours following treatment with ABT-737. Results: ABT-737 was found to inhibit KG-1 cell proliferation at an IC50 of 100 nM following treatment with ABT-737 for 96 hours. The IC50 of the MV-411 cell line was 10 nM after 24 hours of treatment. Molm-13 cells cultured in media containing 10% FCS showed an IC50 of 1 μM at 24 hours following treatment and 100 nM after 48 and 72 hours. Molm-13 cells grown in media containing 1% FCS demonstrated a decrease in percent viability with an IC50 of 100 nM after 24 hours of treatment, 10 nM after 48 hours, and 1 nM after 72 hours following treatment with ABT-737. Conclusions: The AML cell lines KG-1, MV-411, and Molm-13 were susceptible to the pro-apoptotic effects of ABT-737 in vitro. Thus, further investigation into the effects of ABT-737 on additional AML cell lines in vitro and in vivo is warranted. We conclude that ABT-737 either alone or in combination with chemotherapy may provide an alternative mode of therapy for patients with AML.